Mental health, nutritional status, physical activity and healthy eating index among Malaysian university students - Koo H.C.; How Jenniffer S.Y.; Koh J.S.; Law G.S.; Kavisha M Elizabeth (BIO Web of Conferences)
Lifestyle is a complex phenomenon that encompasses all aspects of daily life. University is a crucial period when students are more susceptible to engaging in unhealthy behaviours that can harm their health. This study aimed to assess the mental health, nutritional status, physical activity, and Health Eating Index (HEI) among university students at a university in Klang Valley, Malaysia. In this cross-sectional study, body composition (weight, height, body fat percentage and visceral fat), physical activity (IPAQ questionnaire), healthy eating index (HEI-Malaysia questionnaire) and mental health (GHQ-12 questionnaire) were collected from 383 university students aged 19-30 years using purposive sampling method. Approximately half proportionate of them (n=172; 45%) had unhealthy HEI scores, and 15% of them were overweight/ obese (n=57). However, a majority of them had high physical activity level (n=276; 72.5%). Physical activity was inversely associated with body fat percentage (r=-0.101; p-value<0.05). Meanwhile, GHQ-12 scores were significantly associated with HEI scores (r=0.211; p-value<0.01) and body mass index (r=-0.107; p-value=0.036). The findings of the study indicate that university students are prone to unhealthy eating patterns. Those with good mental health tend to practice healthy eating and have a lower body mass index.